Change in Identity Diffusion and Psychopathology in a Specialized Inpatient Treatment for Borderline Personality Disorder. (21st August 2014) - Sollberger, Daniel; Gremaud‐Heitz, Daniela; Riemenschneider, Anke; Agarwalla, Puspa; Benecke, Cord; Schwald, Oliver; Küchenhoff, Joachim; Walter, Marc; Dammann, Gerhard
Abstract : Objectives: Patients with borderline personality disorder (BPD) show various psychopathological symptoms and suffer especially from disturbance in their identity. The purpose of the study was to investigate changes—particularly in affective BPD symptoms and identity diffusion—during a structured, disorder‐specific inpatient treatment (DST) that combined a psychodynamic transference‐focused psychotherapy approach with modules of dialectical behavioural skills training. Method: In a prospective, two‐group comparison trial, 44 patients with BPD were assessed with questionnaires addressing identity diffusion and state, as well as trait affective psychopathology, before and after 12 weeks of inpatient treatment. Thirty‐two patients received DST, whereas 12 patients were given inpatient treatment‐as‐usual (TAU). The patients were allocated in a non‐random procedure for two groups, in order of admission and availability of treatment options in the DST unit. Results: In the pre‐post‐comparison, the DST group showed a significant decrease in identity diffusion ( p < 0.001) and improvements in instability of the image of self and others ( p < 0.008), as well as in pathological (trait and state) symptoms. However, there was no significant improvement in the TAU group. Conclusions: After a 12‐week inpatient treatment, the findings indicate significant improvements in the DST group in typical affective borderline symptomatology and in the personality structure feature of identity diffusion. This highlights the significance of a short‐term specific inpatient therapy for BPD. Key Practitioner Message: A structured, disorder‐specific inpatient treatment of patients diagnosed with borderline personality disorder (BPD) combined a psychodynamic transference‐focused psychotherapy treatment approach (focusing on pathological features in personality organization, particularly on non‐integrated images of self and others) with modules of dialectical behavioural skills training. This treatment is associated with a decrease in identity diffusion of these patients after 12 weeks of treatment. The treatment is also related to a significant decrease in borderline typical psychopathological symptoms such as depressive symptoms, as well as an improvement in state anger. The outcomes of this structured, disorder‐specific inpatient treatment of severely ill BPD patients indicated the relevance of intensive short‐term inpatient psychotherapy in terms of psychopathological improvements as well as initial changes in structural personality organization. Copyright © 2014 John Wiley & Sons, Ltd.